2020
DOI: 10.1088/1742-6596/1706/1/012159
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent robot-assisted evacuation: A review

Abstract: Mass gathering in places such as shopping mall, concerts, sport events etc. is a necessity but may pose threat to the occupants during emergency. This paper presents a review of the different approaches of the crowd evacuation problems which can be classified into classical and modern methods. The classical methods have been widely used which basically depends on prior evacuation warnings or human in assisting an emergent evacuation scenario. Nonetheless, with the lack of important information such as the loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The literature contains multiple proposals of robots for firefighting. There are reviews on multiple topics, such as fire extinguishing robots (Liu et al, 2016), fire detection sensors (Fonollosa et al, 2018; Gaur et al, 2019), and robot‐assisted evacuation (Bahamid et al, 2020). We have addressed a systematic search of fire detection, monitoring and extinguishing robots, finding the relevant works collected in Table 1.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature contains multiple proposals of robots for firefighting. There are reviews on multiple topics, such as fire extinguishing robots (Liu et al, 2016), fire detection sensors (Fonollosa et al, 2018; Gaur et al, 2019), and robot‐assisted evacuation (Bahamid et al, 2020). We have addressed a systematic search of fire detection, monitoring and extinguishing robots, finding the relevant works collected in Table 1.…”
Section: Literature Reviewmentioning
confidence: 99%
“…• Traditional evacuation strategies: Occupants rely on visual signs, markers, and plans, which determine whether people can safely leave a building (Bahamid et al, 2020) and correct position and visibility according to the emergency plan adopted (Cabinet Office, 2009). Consequently, fire escape routes are frequently marked with visual signs, despite their relatively rapid deterioration in effectiveness with smoke accumulation on the higher part of emergency corridors (Rea et al, 1985;Shell and Matarić, 2005;Ibrahim et al, 2016), and it was demonstrated that people fail to notice and follow them when panicked (Bahamid et al, 2020). Shell and Matarić (2005) demonstrated that even a small number of beacons can help overcome this gap, reducing the expected egress time.…”
Section: Crowd Simulationmentioning
confidence: 99%
“…In addition, they detect and dynamically act according to the environment changes in real-time by considering density, pedestrian flow, and location of the hazard (Tang et al, 2016). Research studies about this field can be divided into three main categories according to the purpose and function of the proposed systems (Bahamid et al, 2020): 1) evacuation guidance systems (Wada and Takahashi, 2013;Ikeda and Inoue, 2016;Zhou et al, 2019), 2) search and rescue systems (Ruangpayoongsak et al, 2005;Murphy et al, 2008;Annuar et al, 2016;Enshasy et al, 2019), and 3) regulation and management of the people flow during evacuation (Boukas et al, 2015;Jiang et al, 2016;Shan et al, 2018;Wan et al, 2020).…”
Section: Crowd Simulationmentioning
confidence: 99%
“…In this section, we discuss the previous studies that focused on implementing distinct techniques and systems for fire detection and an evacuation path. The classic method is widespread and essentially relies on prior evacuation warnings or human assistance in the event of an evacuation scenario; however, the lack of important information such as the safest exit location can be catastrophic [18]. An intelligent evacuation system is the latest approach to a more systematic and simultaneous management of crowds in an emergency [19,20].…”
Section: Literature Reviewmentioning
confidence: 99%